Analysis of Puskesmas Jetis Role in National Strategy TB New Case Prevention - Bianca Gaea Ginting; Happy R Pangaribuan; RE. Judika Tampubolon (Berita Kedokteran Masyarakat (BKM), 2017)
Abstract Background: Control of Tuberculosis relies on Directly Observed Treatment Short Course (DOTS) strategy. This control treatment setting are case management, whereas every year new cases increase signifantly. DOTS strategy is mandatory in every Primary Health Care (Puskesmas) in Indonesia.  Educational Objectives: This paper describes the role and achievement of Puskesmas Jetis in prevention and currative management of TB cases.  Method: Descriptive study with secondary data  Results: It is descriptive analysis with total, 83 cases were assessed from year 2013 to 2016 with 78 patients in TB category I and 5 patients in category II. 27 new cases in 2013, 22 new cases in 2014, 28 new cases in 2015, 25 new cases in 2016. In total 7 patients are children, 69 patients were recovered, 4 patients were in treatment failed status, 4 patients died, and 4 patients were dropped out with cure rate 85,71% in 2015 and 94,11% in 2016.  Conclusions: In DOTS strategy, Puskesmas Jetis has done an effective currative way. It shows in data that from all cases in year 2013 to 2016, more than 70% were recovered. But every year new cases were came out, means Puskesmas Jetis was not succeed in Tuberculosis prevention. Need an improvement on Tuberculosis promotion to prevent overload of new cases every year.  Keywords: Primary Health Care, DOTS strategy, Prevention